Desenvolvimento de uma interface amigável para obtenção e análise de termo fonte para reatores PWR usando o ORIGEN2.1 e o software MATLAB - Joao Paulo Macena Muniz Vieira (2012)
ln the event of an accidental release of radioactive material the source term, i.e., the isotopic composition released tothe environment, should be known as soon as possible to meet the need of mitigating actions So, a quick, clear and safe to al information linked to material released is necessary. Much of codes and programs that calculate the source term do not do so in time for decision making in an emergency situation.This paper describes the initiative to develop a tool in MATLAB that through ORIGEN 2.1 calculate the source term and its features using few computational resources and hence runtime, this tool iscalled TFORI. To accomplish this, the user hasthe possibility to define cells in any quantity in a three dimensional space and run them, each cell will have its own output. This is done in order to obtain more information about a region and reduce computational costs involved. To calculate the source term the user must know the factors of disiribution of power radial and axial of each cell, as well as having the appropriate library for the case studyand the history of reactor operation desired. The validation of the program TFORI was made by comparing the values obtained by it in a case study and the values obtained by ORIGEN2.1 for the same case. There are not losses in the quality of information provided by TFORI. The output was also evaluated by comparing the behavior of nuclides well known from the literature. Finally, a case study using the program TFORI was performed and compared their data with a simulation that used another method. The difference between the results are due to an approximation made to the distribution factor for the axial power by a sine curve and being naturally different methods of calculation. In the future, it is expected the possibility of implementing the results are reused for to achieve an extension in the period of decay as the ORIGEN 2.1 is able to make thisfeedback data.